2013
DOI: 10.1080/02786826.2013.867010
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Soot Deposition in Exhaust Gas Recirculation Coolers Using a Spiral Insert

Abstract: In diesel engines, the emission of nitrogen oxides can profoundly be controlled by using exhaust gas recirculation (EGR) coolers. Nevertheless, the deposition of unwanted materials, in form of primarily particulate matter and hydrocarbons, causes a major hurdle to the durability of such devices. In this study, a novel technique, i.e., a spiral insert, has been developed to mitigate particulate fouling in tubular EGR coolers. It is made of a helical rotating blade which is inserted inside the tubes of EGR coole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…However, the fouling problem in EGR coolers has been an engineering challenge ever since those systems have been introduced. It has been shown that the fouling in EGR coolers reduces their thermo-hydraulic performance over time [3][4][5][6]. Numerous studies have been devoted to investigating this problem during the previous two decades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the fouling problem in EGR coolers has been an engineering challenge ever since those systems have been introduced. It has been shown that the fouling in EGR coolers reduces their thermo-hydraulic performance over time [3][4][5][6]. Numerous studies have been devoted to investigating this problem during the previous two decades.…”
Section: Introductionmentioning
confidence: 99%
“…The exhaust gas is assumed to contain only soot particles and condensation of SOF is neglected which is justifiable for large wall temperatures[8].V. The removal mechanism is ignored because of the low-flow EGR considered[4,11].VI. The thermophoresis is considered as the dominant mechanism for deposition of nano-sized soot particles[11][12][13].VII.…”
mentioning
confidence: 99%